Pogled raziskovalca: načela, metode in prakse - Ambrož, Milan; Colarič-Jakše, Lea-Marija (University of Maribor Press, 2015)
Researcherʼs gaze : principles, methods, and practices. This monograph is different from the similar books in the market, because authors put together a structure that allows the reader to understand how particular concepts go together and make the big picture. Unlike other monographs it is not really about the research methods emphasising the statistical analytic approach. Monograph advances a framework, a process and compositional approaches for designing qualitative, quantitative and in some part mixed methods of research. The red tape in the book derives from the challenging role of the researcher in social and human sciences. This role connects traditional approaches, and qualitative and quantitative research that present mixed methods of research. Monograph explains the creation of a research design and it requires looking from the vantage point of a framework. Besides it concentrates on overall design of a research process and focuses attention to the detail. People who work in academic setting and all other readers alike can learn how to theorize and how to search for answers by reading the mathematical or statistical derivations of the presented interpretations or techniques.